Study of the therapeutic effects of Painong powder on ulcerative colitis and the role of Platycodonis Radix in the prescription based on pharmacodynamic, pharmacokinetic, and tissue distribution analyses. (1st March 2022) - Yu, Hanwen; Sun, Han; Wang, Kang; Liang, Xiao; Ding, Yang; Chang, Xiangwei; Guo, Jian; Peng, Daiyin; Gui, Shuang ying
Abstract: Ethnopharmacological relevance: Herbal formulas have unique efficacy and are of great significance to the theory and practice of Chinese medicine and are therefore gaining increasing attention in research. Painong powder (PNS), composed of Aurantii fructus immaturus (Zhishi in Chinese, ZS), Paeoniae Radix Alba (Baishao in Chinese, BS), and Platycodonis Radix (Jiegeng in Chinese, JG), has remarkable effects on the detoxification and discharge of pus. JG is traditionally used to treat pulmonary carbuncles and is considered a 'medicinal guide'. According to the composition theory of prescriptions, JG is an 'assistant and guide' medicine. The role of JG as an adjuvant has gained increasing attention. Aim of the study: The study was designed to prove the efficacy of PNS in ulcerative colitis (UC) and to study the role of JG in PNS via pharmacodynamic, pharmacokinetic, and tissue distribution analyses. Materials and methods: For the pharmacodynamic study, the UC rat model was induced using 5% trinitrobenzene sulfonic acid (TNBS). The results of the macroscopic characterization, histological analysis, and cytokine levels, including those of tumour necrosis factor-α (TNF-α), interleukin-1β (IL-1β), interleukin-6 (IL-6), and nuclear factor-kappa B (NF-κB), were integrated to evaluate the treatment of UC with PNS. In addition, an LC-MS/MS method was established and validated to analyze the blood pharmacokinetic parameters and tissue distribution of naringin and paeoniflorin. Results: After the administration of high-dose PNS, the UC rats showed amelioration of macroscopic damage at the lesion site. The cytokine levels in the plasma, colon, and lung tissues were also decreased. The pharmacokinetic parameters showed that compared with UC rats administered with PNS-JG, those administered with PNS showed an increase in the AUC, MRT, and Tmax of naringin and paeoniflorin, and a decrease in their clearance rate. Furthermore, naringin and paeoniflorin had higher concentrations in the colon and lung tissues in the normal and model groups administered with PNS than in those administered with PNS-JG. Conclusions: PNS was shown to have marked therapeutic efficacy against TNBS-induced UC in rats. The effect of JG in PNS was reflected by the differences in the pharmacokinetic parameters and tissue distribution of the active components, providing valuable information for the clinical application of PNS in the treatment of UC. However, knowledge about how JG works as an adjuvant medicine in PNS is still lacking. Graphical abstract: Image 1 Highlights: In this study, the efficacy of Painong powder (PNS) in the treatment of ulcerative colitis (UC) was proved by comprehensive macroscopic characterization, histological analysis and cytokine level, including tumor necrosis factor-α (TNF-α), Interleukin-1β (IL-1β), Interleukin-6 (IL-6) and nuclear factor- κB (NF-κB). The LC-MS/MS method was established and validated to analyze the blood pharmacokinetic parameters of naringin and paeoniflorin after treatment with PNS and PNS without JG (PNS-JG). The established LC-MS/MS method was also applied to analyze the distribution of naringin and paeoniflorin in rat colon and lung tissues following treatment with PNS and PNS-JG.